Low prevalence of the BCR–ABL1 fusion gene in a normal population in southern Sarawak - Anselm, Su Ting; Lim, Isabel Fong; Lela, Binti Suut; Jew, Win Kuan; Siow, Phing Tay; Kubota, Sho; Osato, Motomi; Sashida, Goro (Springer Nature Switzerland, 2019)
The BCR–ABL1 fusion gene is the driver mutation of Philadelphia chromosome-positive chronic myeloid leukemia (CML). Its expression level in CML patients is monitored by a real-time quantitative polymerase chain reaction defned by the International Scale (qPCRIS). BCR–ABL1 has also been found in asymptomatic normal individuals using a non-qPCRIS method. In the present study, we examined the prevalence of BCR–ABL1 in a normal population in southern Sarawak by performing qPCRIS for BCR–ABL1 with ABL1 as an internal control on total white blood cells, using an unbiased sampling method. While 146 of 190 (76.8%) or 102 of 190 (53.7%) samples showed sufcient amplifcation of the ABL1 gene at>20,000 or>100,000 copy numbers, respectively, in qPCRIS, one of the 190 samples showed amplifcation of BCR–ABL1 with positive qPCRIS of 0.0023% and 0.0032% in two independent experiments, the sequence of which was the BCR–ABL1 e13a2 transcript. Thus, we herein demonstrated that the BCR–ABL1 fusion gene is expected to be present in approximately 0.5–1% of normal individuals in southern Sarawak.